Development changes in myristoylated alanine-rich C kinase substrate (marcks) phosphorylation expression in rats hippocampus and cortex with acute multi-cerebral infarction and Qingnao drop pilula neuropretection. Issue 2 (2016) - Zhang, Qihui; Zhang, Yunling; Liu, Jing; Bai, Wen; Zhang, Jin; Han, Zhenyun
No abstract available